Reformas necesarias al art. 97 del código del trabajo relacionado a regular el porcentaje de la participación de los trabajadores, en las utilidades de la empresa privada del 15% al 20% - Zambrano Carranza, Karem Elizabeth (2017)
The present investigation work has as purpose to present the environment in which the workers are developed, especially Sacred Domingo’s workers whose socio-economic situation is restricted by insufficient remunerations to the effort that you/they deploy those referred workers, the lack of stimuli in the work by means of additional economic compensations, a participation in utilities that it doesn’t compensate the effort that you/they carry out in no way. This investigation fulfills the academic requirements from the Modality of Studies to Distance of the National University of Loja to more than being an indispensable requirement to approve the present I modulate and this way to be entitled the of continuing to the module immediate superior. The present investigation work analyzes the causes that prevent the workers that you/they perceive remuneration. The investigation confirms the convenience of increasing the percentage of the worker’s participation in the utilities of de companies.